Da representação política no estado democrático de direito - Pinheiro, Arabella Costa (2005)
Political Representation may be adapted to the rnost varied of political regimes, but it is in democracy that its true vocation lies. This is especially so when guided by the fundamental parameters of the Legal State, that is, legality and legitimacy. This study a proaches ali the complexity and magnitude of political representation in the Legal Democratic State. Initially, the construction of philosophical thought on Political Representation in Hobbes, Locke, Rousseau, Montesquieu and Stuart Mil! is analyzed. In this section, the semantic variations and several stages of the concept, the nature and requirements are also investigated. Next, an explanation is given of the entire historical evolution of the Western State, describing the main contributions to the Contemporary State up to the formulation of the Legal Democratic State and the precepts relating to this model of State. Thereafter, a detailed examination is made of Political Representation in the Legal Democratic State, showing the mechanisms which comprise Political Representation and the institutions for direct participation, not neglecting to observe the reality of Brazilian political institutions, looking at the prospects for alterations presented in the Political Reform bill. The study also discusses the evolution of the institution of Representation under Brazilian Constitutional Law and, finally, provides examples of the theme in the light of Comparative Law.